Mind the Eyes: Artificial Agents’ Eye Movements Modulate Attentional Engagement and Anthropomorphic Attribution - Ghiglino, Davide; Willemse, Cesco; De Tommaso, Davide; Wykowska, Agnieszka (Frontiers in Robotics and AI, 2021)
Artificial agents are on their way to interact with us daily. Thus, the design of embodied artificial agents that can easily cooperate with humans is crucial for their deployment in social scenarios. Endowing artificial agents with human-like behavior may boost individuals' engagement during the interaction. We tested this hypothesis in two screen-based experiments. In the first one, we compared attentional engagement displayed by participants while they observed the same set of behaviors displayed by an avatar of a humanoid robot and a human. In the second experiment, we assessed the individuals' tendency to attribute anthropomorphic traits towards the same agents displaying the same behaviors. The results of both experiments suggest that individuals need less effort to process and interpret an artificial agent's behavior when it closely resembles one of a human being. Our results support the idea that including subtle hints of human-likeness in artificial agents' behaviors would ease the communication between them and the human counterpart during interactive scenarios.